2005
DOI: 10.1108/02651330510602204
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of service quality in developed and developing economies: multi‐country cross‐cultural comparisons

Abstract: Purpose -Despite the rapid growth and internationalization of services, marketers of services realize that to successfully leverage service quality as a global competitive tool, they first need to correctly identify the antecedents of what the international consumer perceives as service "quality." This paper aims to examine the differences in perception of service quality dimensions between developed and developing economies. Design/methodology/approach -Parasuraman et al. proposed a framework consisting of te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
241
2
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(267 citation statements)
references
References 63 publications
18
241
2
6
Order By: Relevance
“…Bourdieu"s (1984) perspective concurs in some respects with the, earlier mentioned, study by international marketing researchers Malhotra et al (1994Malhotra et al ( , 2005, who similarly assert that an increase in economic developmental status (i.e. economic capital) results in consumers being less active in evaluating service provider-customer interactions (i.e.…”
Section: "It Is In the Area Of Sociability And The Corresponding Samentioning
confidence: 63%
See 2 more Smart Citations
“…Bourdieu"s (1984) perspective concurs in some respects with the, earlier mentioned, study by international marketing researchers Malhotra et al (1994Malhotra et al ( , 2005, who similarly assert that an increase in economic developmental status (i.e. economic capital) results in consumers being less active in evaluating service provider-customer interactions (i.e.…”
Section: "It Is In the Area Of Sociability And The Corresponding Samentioning
confidence: 63%
“…In conclusion, the body of evidence on social relations within Taiwan suggests that the transformative consequences of a modern developed economy are more complex than suggested by Bourdieu (1984) and Malhotra (2005). Taiwan consumers have not forsaken their extensive social networks as key influences upon their service consumption.…”
Section: Theoretical Implicationsmentioning
confidence: 86%
See 1 more Smart Citation
“…Liu and McClure (2001) focused their research in studying cultural differences in consumer behaviour and found similar outcomes. Malhotra, Ulgado, Agarwal, and Baalbaki, (1994); Malhotra, Ulgado, Agarwal, Shainesh, and Wu, (2005) has proved that there is a difference of perception on service quality among customers in developing and developed nations, they have identified ten factors related to social, cultural and economic environment which play role on customers assessment of service quality perception. The pioneering study done by Hofstede (1991) in which he had studied about national cultures in line with four service quality dimensions of competence, communication, credibility and courtesy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…More studies employ Servqual or modified Servqual to measure banking service quality compared to other measurement tools (Newman & Cowling 1996;Othman & Owen 2001;Han & Baek 2004;Arasli et al 2005a;Muslim & Zaidi 2008;Wong et al 2008;Kanning & Bergmann 2009;Kumar et al 2009;Ladhari 2009;Osman et al 2009;Sadek et al 2010). However, criticisms of the Servqual (Blanchard & Galloway 1994;Gounaris 2005) resulted in the creation of alternative models such as Servperf (Cronin & Taylor 1992;Angur et al 1999;Abdullah et al 2004), Bankserv (Avkiran 1994) and other models (Levesque & McDougall 1996;Stafford 1996;Johnston 1997;Bahia & Nantes 2000;Lassar et al 2000;Aldlaigan & Buttle 2002;Cui et al 2003;Malhotra et al 2005;Mukherjee & Nath 2005;Petridou et al 2007;Guo et al 2008).…”
Section: Literature Review Customer Satisfaction In Banking Literaturementioning
confidence: 99%